KEKUATAN PEMBUKTIAN SURAT PENGAKUAN HAK ATAS TANAH YANG DIKETAHUI OLEH LURAH DAN CAMAT - Hana Wastuti Poetri (Repertorium: Jurnal Ilmiah Hukum Kenotariatan, 2015)
Abstract : Thesis entitled “Strength of Evidence Letter Recognition of Rights (SPH) known by the Village Heads” examine Letter Recognition of Rights (SPH) known by the Village Heads is a form of the physical control of land. Therefore, as a form of administration that has something to do with a verification tool which evidence is to prove the possesion of a land.                The proof here is the physical possesion of a land recognized equivalent, by decree of The Minister of Agrarian incurred as a village chief adjudication team. The strength of Letter Recognition of Rights is seen from various evidence has been qualified as evidence in accordance with those contained in the Civil Code of the Act (vide Article 1874 of the Civil Code), where the existence of a written statement, the witness, the recognition of the parties and the elements contained in the evidence as well as the strength of evidence under the hand.                The existence of A Letter Recognition of Rights as a deed under the hand is as the basis for the issuance of certificates recognized in Government Regulation Number 24 of year 1997 on Land Registration, although the deed under the hand does not have legal force but it can be used as the base in the issuance of certificates and can have the power of legal evidence in court of law. Keywords :       Strength of Evidence, Letter Recognition of Land Rights, Village Heads